2004
DOI: 10.2746/0425164044877189
|View full text |Cite
|
Sign up to set email alerts
|

Hoof wall wound repair

Abstract: Summary Reasons for performing study: Surgical stripping of the hoof wall results in a wound that heals remarkabley well. In contrast, lamellae recovering from laminitis are often deformed. Investigating lamellar wound healing may aid understanding of laminitis. Objectives: To document temporal changes in the lamellar basement membrane (BM), dermis and epidermis after surgery. Methods: Wall strips were made in the dorsal hoof wall midline of 6 mature horses. Immunohistochemistry was used to document changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
1
13
1
Order By: Relevance
“…These findings are consistent with other studies that have reported hyperproliferative wound healing responses within the stratum lamellatum after hoof wall stripping in the normal horse 19 and lamellar histopathology 7 days after experimental induction of laminitis. 20 Consistent with the histologic findings seen in 7-day laminitis is the aberrant nature of the resultant horn production and the abnormal lamellar architecture.…”
Section: Temporal Development Of the Lamellar Wedgesupporting
confidence: 95%
See 1 more Smart Citation
“…These findings are consistent with other studies that have reported hyperproliferative wound healing responses within the stratum lamellatum after hoof wall stripping in the normal horse 19 and lamellar histopathology 7 days after experimental induction of laminitis. 20 Consistent with the histologic findings seen in 7-day laminitis is the aberrant nature of the resultant horn production and the abnormal lamellar architecture.…”
Section: Temporal Development Of the Lamellar Wedgesupporting
confidence: 95%
“…6 and 7). [1][2][3][4]6,18,19 The resultant dysplastic horn structure ( Fig. 8) has been described as ectopic white line, 6 because the histologic appearance (a lamellated array of tubular and nontubular horn) resembles that of the white line, the sole-hoof wall junction, seen in the distal part of the hoof capsule.…”
mentioning
confidence: 99%
“…Despite this, horn restitution appeared to mirror that reported previously (Pollitt and Daradka 2004) and while there is no histological evidence to support complete removal of horn producing tissue in the experimental horses, the presence of the common digital extensor tendon at the bottom of the surgical wound would suggest that total removal had occurred. Epithelialisation from the wound margins must have resulted in restoration of the coronary band.…”
Section: Discussioncontrasting
confidence: 42%
“…The hoof horn was elevated by inserting a curved osteotome into the bottom cut and applying downward pressure to lever the hoof horn upwards from the underlying lamina. The horn was peeled away from the coronary band using a single lateral to medial motion as reported by Pollitt and Daradka (2004). A number 10 scalpel blade was subsequently introduced into the cuts in the hoof horn and used to continue the lines of excision proximally, following the marked line, through the coronary band and into the skin of the distal limb, to the depth of the common digital extensor tendon, extending to a point 1 cm proximal to the upper limit of the coronary band.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation